2013
DOI: 10.1371/journal.pone.0078786
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Unity and Community Empowerment: The Use of Smartphone Technology to Empower Community Management of Chronic Venous Ulcers through the Support of a Tertiary Unit

Abstract: BackgroundChronic ulcers affect roughly 60,000 Irish people, at a total cost of €600,000,000, or €10,000 per patient annually. By virtue of their chronicity, these ulcers also contribute a significant burden to tertiary outpatient vascular clinics.ObjectiveWe propose utilizing mobile phone technology to decentralise care from tertiary centres to the community, improving efficiency and patient satisfaction, while maintaining patient safety.MethodsBespoke mobile software was developed for Apples iPhone 4 platfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…The visiting nurses felt that the new form of communication was an educationally and professionally invigorating process. This perception is in line with other studies Ameen et al found significant improvement in areas of dressings, management and claim, along with Quinn et al, that this translates into a potential beneficial patient related outcome [23][24][25].…”
Section: Discussionsupporting
confidence: 90%
“…The visiting nurses felt that the new form of communication was an educationally and professionally invigorating process. This perception is in line with other studies Ameen et al found significant improvement in areas of dressings, management and claim, along with Quinn et al, that this translates into a potential beneficial patient related outcome [23][24][25].…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, despite the challenges, the home-based care nurses experienced in using telemedicine, they did express the perception that the increased access to specialist healthcare associated with the use of telemedicine had facilitated improvements in their capacity to provide high-quality foot ulcer management in the home-based care context. This is in line with the previous study findings, which identified that applying telemedicine enhanced the healthcare professionals wound care knowledge and skills (Ameen, Coll, & Peters, 2005;Quinn et al, 2013;Rasmussen et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Third, indicators reporting patient centeredness show that centres can improve this measure of quality via increased patient participation and better accessibility of the centre through the use of technologies such as telemedicine .…”
Section: Resultsmentioning
confidence: 99%